THE EFFECT OF INTRINSIC MOTIVATION AND SELF-EFFICACY ON THE NORMATIVE COMMITMENT OF CIVIL SERVANTS IN THE DEPARTMENT OF COOPERATIVES, MICRO ENTERPRISES AND TRADE IN PONTIANAK CITY - Dominikus Rendy Anggara; Irfan Mahdi (Universitas KH. Abdul Chalim Mojokerto, 2026)
Human resources are a vital element in carrying out organizational functions, including in government environments. This research is motivated by fluctuations in discipline and performance of Civil Servants (PNS) at the Office of Cooperatives, Micro Enterprises, and Trade of Pontianak City, which indicates the need to strengthen intrinsic motivation and self-efficacy as internal factors that play a role in employee normative commitment. The main problem in this study is whether there is an influence of intrinsic motivation and self-efficacy on the normative commitment of Civil Servants in the agency. The purpose of this study is to determine the effect of two independent variables, namely intrinsic motivation and self-efficacy, on the dependent variable, namely normative commitment. This study uses an associative quantitative method with a survey approach by distributing questionnaires to 55 Civil Servants as respondents. Data analysis was carried out using multiple linear regression with the help of SPSS software. The results of the study indicate that intrinsic motivation and self-efficacy have a positive and significant effect on normative commitment. Partially, intrinsic motivation has a significant effect with a coefficient of 0.365, while self-efficacy has a greater effect with a coefficient of 0.875. The coefficient of determination (R²) of 0.502 indicates that the two independent variables contribute 50.2% to the normative commitment variable. Thus, increasing employee motivation and self-confidence can strengthen their normative commitment in carrying out organizational duties and responsibilities.